2011
DOI: 10.1097/dbp.0b013e318222355d
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid ADHD and Anxiety Affect Social Skills Group Intervention Treatment Efficacy in Children With Autism Spectrum Disorders

Abstract: Psychiatric comorbidity affects social skill treatment gains in the ASD population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 27 publications
1
84
1
Order By: Relevance
“…Antshel et al have come the closest to testing this research question. In their sample of 83 children (74 males, 9 females) with an ASD (mean age = 9.5 years; SD = 1.2) and common comorbid psychiatric disorders, children with ASD + ADHD benefitted much less from a 10-week social skills training program than children with ASD only and ASD + anxiety disorder [168]. These data suggest that an ASD intervention may not be as effective in the presence of comorbid ADHD.…”
Section: Behavioral Treatmentsmentioning
confidence: 95%
“…Antshel et al have come the closest to testing this research question. In their sample of 83 children (74 males, 9 females) with an ASD (mean age = 9.5 years; SD = 1.2) and common comorbid psychiatric disorders, children with ASD + ADHD benefitted much less from a 10-week social skills training program than children with ASD only and ASD + anxiety disorder [168]. These data suggest that an ASD intervention may not be as effective in the presence of comorbid ADHD.…”
Section: Behavioral Treatmentsmentioning
confidence: 95%
“…For example, work from the National Survey of Children’s Health found that approximately 20% of nearly 1,500 children aged 2–17 with parent-reported ASD were initially given a diagnosis of ADHD, and were diagnosed with ASD three years later than children without ADHD concerns (Miodovnik et al 2015). Studies also indicate differences in response to treatments based on presence/absence of ADHD symptoms in children with ASD (Antshel et al 2011; Cortese et al 2012; Pearson et al 2012; Simonoff et al 2013). Finally, concerns about attention problems, in both those with ASD and their siblings, that persist into middle childhood and school settings also underscore the importance of developing a better understanding of how the two disorders manifest alone and together in childhood (Miller et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of social skills were rated using the Social Skills Rating System (SSRS), a broad measure of social skills, and were compared among children with ASD, ASD plus anxiety, and ASD plus ADHD. Children with ASD and co-occurring ADHD failed to gain social skills, whereas children with ASD without ADHD and children with ASD and anxiety both increased in overall social skills after the intervention [23]. These findings raise a number of questions for future social skills research with this population.…”
Section: Current Researchmentioning
confidence: 81%
“…The majority of treatment-focused research has examined pharmacological treatment via traditional ADHD medication [35]. With respect to psychosocial treatment, very few studies have examined behavioral interventions that directly address cooccurring symptoms, and existing treatment studies have rarely examined outcomes based on co-occurring symptoms profiles [23]. Based on these studies and others, many clinicians and researchers have advocated for changes to the diagnostic criteria to allow co-diagnosis of ADHD and ASD [2,18].…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation